Національна поліція України як суб’єкт протидії нелегальній міграції - Крут, К. О.; Krut, K. O. (Вісник Харківського національного університету внутрішніх справ. – 2023. – № 3 (102), ч. 1. - С. 111-120, 2023)
Охарактеризовано повноваження такого суб’єкта протидії нелегальній міграції, як Національна поліція України. Наголошено, що нелегальна міграція – це негативне явище, яке потребує вжиття спеціально уповноваженими суб’єктами скоординованого комплексу заходів задля запобігання та протидії цьому процесу. Класифіковано повноваження щодо протидії нелегальній міграції на загальні та спеціальні залежно від структурного підрозділу Національної поліції України, який їх виконує. Визначено, що основним підрозділом, який безпосередньо наділений повноваженнями з реалізації державної політики у сфері протидії нелегальній міграції, є Департамент (Управління) міграційної поліції, який входить до складу кримінальної поліції. До повноважень цього органу віднесено організаційні, попереджувальні й адміністративно-правові заходи щодо протидії нелегальній міграції.

The article describes the powers of the National Police of Ukraine to combat illegal migration. Since illegal migration is a negative phenomenon that requires a comprehensive, mutual and coordinated set of measures by all specially authorised actors in the field of combating illegal migration to prevent and counteract this process. The National Police of Ukraine, in our opinion, is one of the main actors in countering this phenomenon. We classified the powers to combat illegal migration into general and special, depending on the structural unit of the National Police of Ukraine that carries them out. The subdivision, which is directly empowered to implement state policy in the field of countering illegal migration, as well as bringing to administrative responsibility for violations of legislation in the field of registration of natural persons, issuance of documents certifying identity and confirming citizenship, belongs to the Department (Office) of the Migration Police, which includes to the criminal police. Their scope of authority includes organizational, preventive and administrative-legal measures to combat illegal migration. The National Police of Ukraine, which is endowed with an exhaustive list of powers that currently require expansion and modernization. First of all, it is very important to coordinate the mutual activities of all subjects of combating illegal migration and to adopt relevant legal acts. Secondly, it is necessary to improve and expand the scope of powers of the Department (Office) of the Migration Police to bring to justice foreigners who violate the migration legislation of Ukraine, for quick response to administrative and criminal offenses. This article has a scientific and theoretical significance based on the relevance of illegal migration in our country and combating human trafficking as one of the factors that threaten national security and law and order.

Охарактеризованы полномочия такого субъекта противодействия нелегальной миграции, как Национальная полиция. Отмечено, что нелегальная миграция – это негативное явление, которое требует принятия специально уполномоченными субъектами скоординированного комплекса мер по предотвращению и противодействию этому процессу. Классифицировано полномочия по противодействию нелегальной миграции на общие и специальные в зависимости от структурного подразделения Национальной полиции Украины, которое их выполняет. Определено, что основным подразделением, непосредственно наделенным полномочиями по реализации государственной политики в сфере противодействия нелегальной миграции, является Департамент (Управление) миграционной полиции, входящей в состав уголовной полиции. К полномочиям этого органа отнесены организационные, предупредительные и административно-правовые мероприятия по противодействию нелегальной миграции.
The National Police of Ukraine as an object to combat illegal migration
Keywords: протидія нелегальній міграції; Національна поліція України; повноваження; правоохоронні органи; Департамент міграційної поліції; національна безпека; combating illegal migration; National Police of Ukraine; powers; law enforcement agencies; Migration Police Department; national security; противодействие нелегальной миграции; Национальная полиция Украины; полномочия; правоохранительные органы; Департамент миграционной полиции; национальная безопасность